Recognise and Acknowledge Us: Views of Traditional Birth Attendants on Collaboration with Midwives for Maternal Health Care Services - Musie, Maurine Rofhiwa; Mulaudzi, Mavis Fhumulani; Anokwuru, Rafiat; Bhana-Pema, Varshika (International Journal of Reproductive Medicine, 2022)
Background. Traditional birth attendants have since ancient time provided care to pregnant women. As such, the collaboration between midwives and traditional birth attendant (TBAs) can be an essential effort towards the reduction of the maternal and neonatal mortality and morbidity rate especially in low- and middle-income countries (LMICs). This paper argues that the collaboration between traditional and formal health systems expands the reach and improves outcomes of community health care. The study is aimed at exploring the traditional birth attendant’s views on collaboration with midwives for maternal health care services at selected rural communities in South Africa (SA). Methods. The study was conducted in two rural communities in Tshwane and Johannesburg metropolitan districts from 15 June to 31 October 2021. The study followed the qualitative explorative and descriptive research design. The sampling technique was nonprobability purposive, and snowballing technique was also used to sample the key informants who are the traditional birth attendants also known as traditional healers and who provide maternal health care services in the respective communities. The access to these participants was through the gatekeepers, the Traditional Health Organisation Council (THO) council. Data collection was through semistructured in-depth interviews. Data were analysed thematically through the eight steps of Tesch. Results. Five main themes were identified which included the recognition of traditional birth attendants as enablers of collaboration, the envisaged value of the collaboration, processes required to foster collaboration, repositioning for new roles, and barriers to collaboration. Conclusion. The TBAs are ready to collaborate with the formal health care system, and all they require is for their services to maternal health care to be recognised and acknowledged.